Understanding the Role of Automated Writing Tools: A Library Research on Grammarly in Academic Writing - Patty, Jusak (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This library research investigates the pedagogical implications and complexities of implementing Grammarly as an automated writing assistant in academic contexts. The systematic analysis of peer-reviewed literature examines the multifaceted relationship between automated feedback systems and writing development, focusing on user engagement patterns, writing quality outcomes, and institutional implementation frameworks. The investigation reveals sophisticated patterns of interaction between technological affordances and established pedagogical practices, where successful integration depends on carefully calibrated implementation strategies that acknowledge immediate practical needs and long-term educational objectives. Findings indicate that while automated writing assistance effectively addresses surface-level writing concerns, its impact on higher-order writing development emerges through complex interactions between user proficiency, institutional support structures, and pedagogical frameworks. The research demonstrates that optimal outcomes occur when automated feedback complements traditional writing instruction through structured implementation approaches guided by informed pedagogical principles. Analysis of longitudinal engagement patterns reveals how sustained interaction with automated feedback catalyzes the development of sophisticated writing strategies and enhanced metalinguistic awareness, mainly when supported by robust institutional frameworks. The study identifies critical challenges in maintaining an appropriate balance between technological assistance and independent writing skill development while highlighting opportunities for innovative pedagogical approaches that leverage automated feedback to enhance writing instruction. These findings contribute to a deeper understanding of how automated writing assistance can be effectively integrated into academic writing instruction while preserving essential pedagogical principles, providing valuable insights for educators and institutions seeking to implement these tools within comprehensive writing support frameworks.